“Somos libres, seámoslo siempre”. Sobre la música en tiempos de la independencia del Perú: Entrevista al doctor Eduardo Torres Arancivia - de Belaunde, Carolina (Notas de Antropología de las Américas, 2023)
The lyrics of the Peruvian national anthem —written by José de la Torre Ugarte and musicalized by José Bernardo Alzedo in 1821— sing to freedom, equality, happiness and unity. “We are free, let us always be” are words that we need to remember and reaffirm frequently, especially during times of social and political turmoil. Approaching the bicentennial of the independence of the country, we interviewed Historian Eduardo Torres Arancivia about the music that accompanied the first years of the novel republic. With his characteristic rigor, Torres Arancibia offers us a valuable contribution on a little-studied subject: the context, the emotional power and the importance that music had within the promise of nation-building in Peru.